(2/7)x=6/11

Simple and best practice solution for (2/7)x=6/11 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2/7)x=6/11 equation:



(2/7)x=6/11
We move all terms to the left:
(2/7)x-(6/11)=0
Domain of the equation: 7)x!=0
x!=0/1
x!=0
x∈R
We add all the numbers together, and all the variables
(+2/7)x-(+6/11)=0
We multiply parentheses
2x^2-(+6/11)=0
We get rid of parentheses
2x^2-6/11=0
We multiply all the terms by the denominator
2x^2*11-6=0
Wy multiply elements
22x^2-6=0
a = 22; b = 0; c = -6;
Δ = b2-4ac
Δ = 02-4·22·(-6)
Δ = 528
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{528}=\sqrt{16*33}=\sqrt{16}*\sqrt{33}=4\sqrt{33}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(0)-4\sqrt{33}}{2*22}=\frac{0-4\sqrt{33}}{44} =-\frac{4\sqrt{33}}{44} =-\frac{\sqrt{33}}{11} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(0)+4\sqrt{33}}{2*22}=\frac{0+4\sqrt{33}}{44} =\frac{4\sqrt{33}}{44} =\frac{\sqrt{33}}{11} $

See similar equations:

| x=0.01x500 | | 6=n-5 | | (3x+33)/3=51 | | 4t–3=2t+7 | | 2=-8x-14 | | 7=v/13.4 | | x+12=8x+5 | | 5+9t=+3 | | 1/2y-4=8 | | 7=v13.4 | | 5a–3=2a+6 | | g÷4−1=2 | | 6x-9=3(3+x) | | (3x-5)+7x+5=180 | | -(6x+)=4(17-x) | | Rx10=40 | | x+4/5=(1/4)x-4/10 | | 3x+33/3=51 | | 2(3y-7)=40 | | 5(x+4)=5x+3x-1 | | 4w=138 | | 4w=136 | | 12=x10 | | 2(8-t)=5t+9 | | 2.86x=4.34 | | 3x-5=-42 | | –2x+1=13 | | 9.5x=80 | | 11(k-3)=34 | | 12=(2n-6)/4 | | x+-21=x | | 75=5v+11 |

Equations solver categories